Detection of Anaplasma phagocytophilum, Candidatus Neoehrlichia sp., Coxiella burnetii and Rickettsia spp. in questing ticks from a recreational park, Portugal - Santos, A.S. (2019)
Tick-borne agents with medical relevance have been recorded in Portugal but little is known about their oc-currence in urban outdoor leisure areas. This study aimed to investigate ticks and tick-borne agents in threepublic parks of Lisbon’s metropolitan area. A total of 234 questing ticks belonging to eight species were found inParque Florestal de Monsanto (PFM). Ixodes ventalloi represented 40% of collections. Mitochondrial genesconﬁrmed Ixodes morphological identiﬁcation, evidencing the intraspeciﬁc variability of I. ricinus and particu-larly I. frontalis populations. Regarding tick-borne agents, Rickettsia massiliae DNA were found in 21 (9.0%) ticks,Coxiella burnetii in 15 (6.4%), Anaplasma phagocytophilum in ﬁve (2.1%), an agent closely related to CandidatusNeoehrlichia mikurensis in two (0.9%), Rickettsia sibirica mongolitimonae and Rickettsia monacensis each in one(0.4%). Active enzootic cycles were suggested for these agents by the detection of positives in diﬀerent timeperiods. Five tick species were founded with C. burnetii, including I. ventalloi which seems to be a new associationrecord. This tick was also the only species found positive for A. phagocytophilum and the Candidatus Neoehrlichiamikurensis-like agent. Two A. phagocytophilum variants were detected in PFM, one of them representing a po-tentially new ecotype already found in I. ventalloi from another Portuguese area. To the authors´ knowledge, thisis also the ﬁrst report of such a Candidatus Neoehrlichia mikurensis-like microorganism. These data show aninteresting diversity of ticks and tick-borne agents with potential public health relevance in PFM, an urbanrecreational area commonly frequented by humans and their pets.